A localized PCR inhibitor in a porcelain crab suggests a protective role - Mahmoud A. El-Maklizi; Amged Ouf; Ari Ferreira; Shahyn Hedar; Edwin Cruz-Rivera (PeerJ, 2014)
A number of polymerase chain reaction (PCR) inhibitors have been identified from biological and environmental samples. By and large, such substances are treated as random nuisances and contaminants with alternate functions; their inhibitory effects on DNA replication being a coincidental property of their molecular structure. Here, we demonstrate the presence of a localized PCR inhibitor in the foregut of the porcelain crab Petrolisthes rufescens (Anomura: Porcellanidae) from the Red Sea. The inhibitor precluded amplification of 28s, 16s and 18s gene sequences effectively but lost activity at 10−2 dilutions from initial concentration. Heat treatment was ineffective in arresting inhibition and spectrophotometric techniques suggested that the inhibitor was not a melanin-type compound. The compound was not detected from midgut, hindgut, or gills of the crab. Activity of the inhibitor was precluded when samples were treated with suspensions from the midgut, suggesting that enzymatic degradation of the inhibitor likely happens at that part of the gut. As many microbial pathogens invade their hosts via ingestion, we suggest the presence of the localized inhibitor could carry a defensive or immunological role for P. rufescens. The identity of the inhibitory molecule remains unknown.